2019
DOI: 10.3390/cryst9020087
|View full text |Cite
|
Sign up to set email alerts
|

Nanowires for High-Efficiency, Low-Cost Solar Photovoltaics

Abstract: Solar energy is abundant, clean, and renewable, making it an ideal energy source. Solar cells are a good option to harvest this energy. However, it is difficult to balance the cost and efficiency of traditional thin-film solar cells, whereas nanowires (NW) are far superior in making high-efficiency low-cost solar cells. Therefore, the NW solar cell has attracted great attention in recent years and is developing rapidly. Here, we review the great advantages, recent breakthroughs, novel designs, and remaining ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 218 publications
0
46
0
Order By: Relevance
“…To realize advanced devices in a NW configuration successfully, dopant incorporation with abrupt interfaces in a well-controlled manner is essential and enables one to modulate work functions. Unfortunately, the thin film studies on dopant incorporation and carrier concentration cannot be directly translated to NWs due to the dopant’s influence on the growth kinetics and different growth mechanisms along with the axial and radial directions 3 . Also, the commonly used measurement techniques in thin films for the determination of carrier concentration, namely Hall effect, field-effect, capacitance–voltage, and thermoelectric measurements, require highly sophisticated lithography steps 4 10 .…”
Section: Introductionmentioning
confidence: 99%
“…To realize advanced devices in a NW configuration successfully, dopant incorporation with abrupt interfaces in a well-controlled manner is essential and enables one to modulate work functions. Unfortunately, the thin film studies on dopant incorporation and carrier concentration cannot be directly translated to NWs due to the dopant’s influence on the growth kinetics and different growth mechanisms along with the axial and radial directions 3 . Also, the commonly used measurement techniques in thin films for the determination of carrier concentration, namely Hall effect, field-effect, capacitance–voltage, and thermoelectric measurements, require highly sophisticated lithography steps 4 10 .…”
Section: Introductionmentioning
confidence: 99%
“…This S-shape of the JÀV curve is a sign of non-optimal carrier collection in the device that results from the defects in the solar cell layers [36][37][38]. Many different solar cell designs based on nanomaterials and nanotextures have been reported that decouple light absorption and carrier extraction leading to increased efficiency [39]. In the case of the IP-SC and other such rough textures, the intended optical benefit is obtained due to the increased scattering induced by the textures, but it is often at the cost of the electrical performance due to shunts and defects associated with the rough interfaces of the solar cell layers.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that currently nanowire solar cells have achieved high efficiency: 10.2 % for horizontal structures and 40.0 % for vertical ones [10], which contributes to the development of new high-efficiency and low-cost nanowire photovoltaic converters [10][11][12], in particular, tandem or axially tandem, branched, inorganic/organic hybrid, on flexible substrates and substrates of glass, amorphous silicon, graphene, carbon nanotubes, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The constant search for improving solar energy collection methods using photovoltaic converters causes considerable interest in coaxial p-i-n structures based on nanowires and in the study of their properties and characteristics [10][11][12]. Nanowire arrays have optimal capture of a wide part of the solar spectrum, which provides efficient collection of solar energy and the minimum diffusion path length of charges, etc.…”
Section: Introductionmentioning
confidence: 99%